2020
DOI: 10.1186/s13011-020-00271-9
|View full text |Cite
|
Sign up to set email alerts
|

Treatment adherence amongst drug users attending public and private methadone maintenance clinics in a northern province of Vietnam

Abstract: Background: Methadone maintenance treatment (MMT) has been proven to be effective in improving health status and the quality of life of illicit drug users. Due to the quick expand of methadone program, socialization through co-payment service is a critical to the success of it. In Nam Dinh, Vietnam, MMT has been used in public clinics and one private clinic. Such effectiveness of this treatment has been found to depend largely on adherence to treatment. This study aims to explore the compliance rate and its in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 41 publications
3
7
1
Order By: Relevance
“…Regarding the bibliographic search, there are numerous and varied studies [24][25][26][27][28][29][30][31][32][33][34][35][36] in the literature from different geographical areas, mainly Asian, Canadian and American, from different healthcare settings, mainly involving outpatients in detoxification clinics and community pharmacies, that investigate different issues related to adherence to methadone maintenance treatment (MMT). However, the main limitation of these studies is that they interchangeably express adherence or retention to MMT or MMP, the latter including interventions beyond the mere collection of daily methadone doses.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the bibliographic search, there are numerous and varied studies [24][25][26][27][28][29][30][31][32][33][34][35][36] in the literature from different geographical areas, mainly Asian, Canadian and American, from different healthcare settings, mainly involving outpatients in detoxification clinics and community pharmacies, that investigate different issues related to adherence to methadone maintenance treatment (MMT). However, the main limitation of these studies is that they interchangeably express adherence or retention to MMT or MMP, the latter including interventions beyond the mere collection of daily methadone doses.…”
Section: Resultsmentioning
confidence: 99%
“…As being aware of challenges ahead regarding limited resources and healthcare capacities ( 31 ), the Government of Vietnam had implemented various mandatory measures in the early phase of the epidemic to “flattening the curve” ( 32 ). It is necessary for the government to have time for preparing a possible upsurge in the number of COVID-19 cases and forecasting the pandemic peak in the next stages ( 13 , 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from our study indicated a significantly high agreement about the importance of response measures that the Government performed during the epidemic. This phenomenon can be explained that along with the role of the Government's leadership, the transparency in epidemic information and the great involvement of mass media were critically important in developing the beliefs of the community in the Government's actions, and the importance of changing behaviors such as wearing masks, good hygiene, social distancing, or compulsory quarantine ( 32 , 35 , 36 ). Our study implied a high acceptance and feasibility of these measures if they had to be performed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Poor relationships with service providers and insufficient information about treatment services contribute to suboptimal treatment adherence and retention among Vietnamese PLHWUD. 3336 Comprehensive services and support from commune health workers (CHW) have been suggested as vital ingredients in improving Vietnam’s drug- and HIV-related service satisfaction levels. 3739…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Poor relationships with service providers and insufficient information about treatment services contribute to suboptimal treatment adherence and retention among Vietnamese PLHWUD. [33][34][35][36] Comprehensive services and support from commune health workers (CHW) have been suggested as vital ingredients in improving Vietnam's drug-and HIVrelated service satisfaction levels. [37][38][39] To strengthen community capacity in providing accessible treatment services for PLHWUD, our team developed and implemented an intervention program in Vietnam to equip CHW with communication skills and tools to motivate PLHWUD in the community to seek and retain in healthcare services.…”
Section: Introductionmentioning
confidence: 99%